2009
DOI: 10.1017/s0021932009990381
|View full text |Cite
|
Sign up to set email alerts
|

Using a Reproductive Life Course Approach to Understand Contraceptive Method Use in Australia

Abstract: This paper examines contraceptive method use at different stages of the reproductive life course. Previous research on contraceptive practice in developed countries typically applies age as a proxy for reproductive history. While age is an essential and useful life course measure for understanding contraceptive use, investigations of contraceptive practice should also consider parity and fertility intentions, as they may be more accurate measures of reproductive life course stage. Analysis is based on data col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 7 publications
2
28
1
1
Order By: Relevance
“…The fertility increase has occurred despite an ongoing, if slower, decrease in the prevalence of marriage in the reproductive age groups and slight improvements in the availability and use of contraceptive methods (Birrell, Rapson, and Hourigan 2004;Parr and Siedlecky 2007;Heard 2008;Gray and McDonald 2010). The effect of the decrease in marriage on rates of partnership has been offset partially by increases in the percentages of females in unmarried cohabitation.…”
Section: Proximate Determinants Of Australia's Fertility Increasementioning
confidence: 99%
“…The fertility increase has occurred despite an ongoing, if slower, decrease in the prevalence of marriage in the reproductive age groups and slight improvements in the availability and use of contraceptive methods (Birrell, Rapson, and Hourigan 2004;Parr and Siedlecky 2007;Heard 2008;Gray and McDonald 2010). The effect of the decrease in marriage on rates of partnership has been offset partially by increases in the percentages of females in unmarried cohabitation.…”
Section: Proximate Determinants Of Australia's Fertility Increasementioning
confidence: 99%
“…In these latter countries, married and cohabiting female contraceptors were most likely to rely on highly-effective reversible (HER) methods, such as pills and IUDs (see Table 2). Lower use of HER methods (particularly IUDs) in the United States and Australia (Eeckhaut, Sweeney, and Gipson 2014) may be related to the poor reputation and subsequent distrust of IUDs after reports of serious safety concerns with the Dalkon Shield IUD in the 1970s (Hubacher and Cheng 2004; Gray and McDonald 2010). As the Dalkon Shield was seldom used in Europe, the safety scare associated with this device likely had less of an impact on contraceptive use patterns in Europe (Sonfield 2007).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In the United States, limited evidence suggests that socioeconomic differentials in parity contribute to, but do not fully explain, associations between the prevalence of surgical sterilization and education or income at the time of interview (e.g., Chandra 1998; Eisenberg et al 2009; Anderson et al 2012). In Australia, Gray and McDonald (2010) found the negative link between a woman’s education and her reliance on contraceptive sterilization (male or female methods, combined) to become non-significant when adding controls for factors such as parity and relationship status. In Northern Belgium (Flanders), Lodewijckx (2002) found that relatively lower levels of sterilization (again, male or female methods combined) among couples where at least one partner had completed higher education persist even after controlling for background factors such as parity and age at last birth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Um dos pressupostos que fundamenta o uso das trajetórias na investigação em saúde é o reconhecimento da complexidade que envolve o tema. Práticas e concepções relativas à saúde variam ao longo do tempo e do momento da vida de cada um; entretanto, uma ação ou decisão tomada num dado momento interfere no curso da vida e determina situações posteriores 3 . Ao mesmo tempo, estas ações e decisões se inscrevem em contextos de vida marcados social e culturalmente, que circunscrevem as possibilidades de escolhas e atribuem sentidos a estas, delimitando capacidades e recursos para o manejo das situações vivenciadas 4 .…”
Section: Introductionunclassified